L'anno della morte di Luigi Crocetti Un racconto di biblioteconomia - Cheti, Alberto (Biblioteche & bibliotecari / Libraries & librarians, 2021)
The story evokes an imaginary dialogue between a student and the master, after his death. The master is Luigi Crocetti, a well-known and unforgettable figure in the world of libraries. He was a librarian at the National Central Library of Florence, scholar and teacher of librarianship, president of the Italian Library Association in the 1980s. The master's death arouses in the student the desire to carry on a conversation with him about libraries and in particular about subject cataloguing. In these talks, the proposed themes are accompanied by feelings, memories, descriptions of landscapes, simple and naive reflections about life questions. Both of them intend to dispose the story's protagonist and the reader to listen to the master's lesson again. Although in narrative form, this text reviews some key passages of the Crocetti's writings and also intends to contribute to the reconstruction of his intellectual biography. Some essays by the author about his thought and work are reproduced in the appendix.